In Central Obesity, Weight Loss Restores Platelet Sensitivity to Nitric Oxide and Prostacyclin - Russo, Isabella; Traversa, Monica; Bonomo, Katia; De Salve, Alessandro; Mattiello, Luigi; Del Mese, Paola; Doronzo, Gabriella; Cavalot, Franco; Trovati, Mariella; Anfossi, Giovanni (Obesity (Silver Spring, Md.), 2010)
Central obesity shows impaired platelet responses to the antiaggregating effects of nitric oxide (NO), prostacyclin, and their effectors—guanosine 3′,5′-cyclic monophosphate (cGMP) and adenosine 3′,5′-cyclic monophosphate (cAMP). The influence of weight loss on these alterations is not known. To evaluate whether a diet-induced body-weight reduction restores platelet sensitivity to the physiological antiaggregating agents and reduces platelet activation in subjects affected by central obesity, we studied 20 centrally obese subjects before and after a 6-month diet intervention aiming at reducing body weight by 10%, by measuring (i) insulin sensitivity (homeostasis model assessment of insulin resistance (HOMAIR)); (ii) plasma lipids; (iii) circulating markers of inflammation of adipose tissue and endothelial dysfunction, and of platelet activation (i.e., soluble CD-40 ligand (sCD-40L) and soluble P-selectin (sP-selectin)); (iv) ability of the NO donor sodium nitroprusside (SNP), the prostacyclin analog Iloprost and the cyclic nucleotide analogs 8-bromoguanosine 3′,5′-cyclic monophosphate (8-Br-cGMP) and 8-bromoadenosine 3′,5′-cyclic monophosphate (8-Br-cAMP) to reduce platelet aggregation in response to adenosine-5-diphosphate (ADP); and (v) ability of SNP and Iloprost to increase cGMP and cAMP. The 10 subjects who reached the body-weight target showed significant reductions of insulin resistance, adipose tissue, endothelial dysfunction, and platelet activation, and a significant increase of the ability of SNP, Iloprost, 8-Br-cGMP, and 8-Br-cAMP to reduce ADP-induced platelet aggregation and of the ability of SNP and Iloprost to increase cyclic nucleotide concentrations. No change was observed in the 10 subjects who did not reach the body-weight target. Changes of platelet function correlated with changes of HOMAIR. Thus, in central obesity, diet-induced weight loss reduces platelet activation and restores the sensitivity to the physiological antiaggregating agents, with a correlation with improvements in insulin sensitivity.